COMPUTER VISION FOR BODY WEIGHT ESTIMATION - BENAISSA, AYA; BENAISSA, DOUNIA HANAA; Ghemougui, Abdessattar: Reporter (UNIVERSITY OF MOHAMED BOUDIAF – MSILA, FACULTY OF MATHEMATICS AND COMPUTER SCIENCE, DEPARTMENT OF COMPUTER SCIENCE, 2024)
Computer vision-based weight estimation is a field of research that aims to estimate the weight of an object, animal, or human using computer vision techniques. This method uses image processing algorithms and 3d reconstruction methods to extract relevant features from images and perform weight prediction using a convolutional neural network and transfer learning
Keywords: Weight estimation; Computer vision; Machine learning; Deep learning; CNN; Transfer Learning